Functional Characterization of a Hexose Transporter from Root Endophyte Piriformospora indica - Rani, Mamta; Raj, Sumit; Dayaman, Vikram; Kumar, Manoj; Dua, Meenakshi; Johri, Atul K. (Frontiers in Microbiology, 2016)
Understanding the mechanism of photosynthate transfer at symbiotic interface by fungal monosaccharide transporter is of substantial importance. The carbohydrate uptake at the apoplast by the fungus is facilitated by PiHXT5 hexose transporter in root endophytic fungus Piriformospora indica. The putative PiHXT5 belongs to MFS superfamily with twelve predicted transmembrane helices. It possesses sugar transporter PFAM motif (PF0083) and MFS superfamily domain (PS50850). It contains the signature tags related to glucose transporter GLUT1 of human erythrocyte. PiHXT5 is regulated in response to mutualism as well as glucose concentration. We have functionally characterized PiHXT5 by complementation of hxt-null mutant of Saccharomyces cerevisiae EBY.VW4000. It is involved in transport of multiple sugars ranging from D-glucose, D-fructose, D-xylose, D-mannose, D-galactose with decreasing affinity. The uncoupling experiments indicate that it functions as H+/glucose co-transporter. Further, pH dependence analysis suggests that it functions maximum between pH 5 to 6. The expression of PiHXT5 is dependent on glucose concentration and was found to be expressed at low glucose levels (1 mM) which indicate its role as a high affinity glucose transporter. Our study on this sugar transporter will help in better understanding of carbon metabolism and flow in this agro-friendly fungus.